Inhalts- und Nebenbestimmungen in Genehmigungen von Windenergieanlagen Rechtliche Zulässigkeit und betriebswirtschaftliche Auswirkungen - Frey, Michael (2022)
Following a legal and economic evaluation of all wind turbine autorisations issued in Baden-Württemberg between 2012 and 2017, this working aid shows - in addition to the requirements to be observed - optimal text modules for side regulations in all relevant legal areas. It thus offers an indispensable working aid in the important field of the legally secure expansion of wind energy - this also beyond the borders of the administrative practice in Baden-Württemberg.